ActA promotes Listeria monocytogenes aggregation, intestinal colonization and carriage. - Laetitia Travier (Public Library of Science (PLoS), 2013)
Listeria monocytogenes (Lm) is a ubiquitous bacterium able to survive and thrive within the environment and readily colonizes a wide range of substrates, often as a biofilm. It is also a facultative intracellular pathogen, which actively invades diverse hosts and induces listeriosis. So far, these two complementary facets of Lm biology have been studied independently. Here we demonstrate that the major Lm virulence determinant ActA, a PrfA-regulated gene product enabling actin polymerization and thereby promoting its intracellular motility and cell-to-cell spread, is critical for bacterial aggregation and biofilm formation. We show that ActA mediates Lm aggregation via direct ActA-ActA interactions and that the ActA C-terminal region, which is not involved in actin polymerization, is essential for aggregation in vitro. In mice permissive to orally-acquired listeriosis, ActA-mediated Lm aggregation is not observed in infected tissues but occurs in the gut lumen. Strikingly, ActA-dependent aggregating bacteria exhibit an increased ability to persist within the cecum and colon lumen of mice, and are shed in the feces three order of magnitude more efficiently and for twice as long than bacteria unable to aggregate. In conclusion, this study identifies a novel function for ActA and illustrates that in addition to contributing to its dissemination within the host, ActA plays a key role in Lm persistence within the host and in transmission from the host back to the environment.